2017
DOI: 10.17576/gema-2017-1704-15
|View full text |Cite
|
Sign up to set email alerts
|

Strategi dan Teknik Terjemahan Novel Arab dalam Kalangan Pelajar Universiti (Arabic Novel Translation Strategies and Techniques used among University Students)

Abstract: Strategi Pembelajaran Terjemahan (SPT) ini agak tersisih daripada arus pendekatan komunikatif dalam kurikulum bahasa Arab, namun para sarjana mengakui ia adalah strategi dominan yang diperlukan terutama kepada pelajar bahasa ketiga yang masih di peringkat keupayaan yang sederhana. Kajian ini bertujuanmengenal pasti tahap penggunaan strategi terjemahan dalam pembelajaran bahasa Arab secara keseluruhan dan mengikut klasifikasi secara spesifik, danmengkategori jenis teknik terjemahan novel Arab dalam kalangan pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The influence of anxiety in Arabic language learners' environment particularly in foreign language learners' situation is put in to consideration by many researchers (Bahraudin, 2017). However, researchers like Haron et al, (2016) declared that Arabic students with peak language anxiety levels might have low language achievement.…”
Section: Factors Affecting the Listening Skillsmentioning
confidence: 99%
See 3 more Smart Citations
“…The influence of anxiety in Arabic language learners' environment particularly in foreign language learners' situation is put in to consideration by many researchers (Bahraudin, 2017). However, researchers like Haron et al, (2016) declared that Arabic students with peak language anxiety levels might have low language achievement.…”
Section: Factors Affecting the Listening Skillsmentioning
confidence: 99%
“…Though, wan (2016) found that listening ability is tremendously anxiety frustrating mostly when the text is not comprehensible to the learners. Students regularly sensed nervous if listening in the target language for the reason that several factors for example the legality of the listening script (Bahraudin, 2017). Even though unidentified or rigid sentence used in the script, peculiarity of the listening substantial for the environmental factors for instance accent, and learners' lack of self-reliance in their listening ability (Yan & Wan, 2018).…”
Section: Factors Affecting the Listening Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent developments, Arabic has finally got very significant attention from scientists and reviewers of Islamic studies in many fields. Many of these studies were related to the innovation of strategies in teaching Arabic in different contexts and language skills (W. Baharudin, 2017;Fajriah, 2017;M. Khalilullah, 2011;Sangid & Muhib, 2019); approaches or teaching designs (Muradi, 2014;Shodiq, 2018;Ummi & Mulyaningsih, 2016); media (Azhari, 2015;Iswanto, 2017;Mahmudah, 2018); and some external influences in teaching and learning Arabic (Abdullah et al, 2015;Kassim et al, 2017;Wekke, 2016) which have been included as a part of formal and non-formal education curriculum.…”
Section: A Introductionmentioning
confidence: 99%